2007
DOI: 10.1016/j.nucmedbio.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

5-Chloro-2-(2′-((dimethylamino)methyl)-4′-iodophenylthio)benzenamine: a new serotonin transporter ligand

Abstract: Two novel ligands with a 4′-substitution on the phenyl ring B of biphenylthiol: 5-chloro-2-(2′-((dimethylamino)methyl)-4′-iodophenylthio)benzenamine, 7, and 2-(2′-((dimethylamino) methyl)-4′-methoxyphenylthio)-5-iodobenzenamine, 8, were prepared and tested as potential serotonin transporter (SERT) imaging agents. The new ligands displayed extremely high binding affinities to SERT (K i = 0.22 ± 0.09 and 0.11 ± 0.04 nM, respectively), with very low binding affinities to dopamine and norepinephrine transporters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…These cells are grown and maintained in our laboratory providing a convenient source of specific DAT, SERT or NET protein for in vitro binding assays. Because it is easy, readily available and provides comparable data for in vitro binding assays, our lab has used the cells expressing the specific transporter instead of membrane homogenates of rat frontal cortex or striatum to screen monoamine transporter inhibitors [29]. The compounds 8-11 synthesized and reported in this paper were subjected to binding evaluations for the monoamine transporters NET, SERT and DAT.…”
Section: Biological Evaluationsmentioning
confidence: 99%
“…These cells are grown and maintained in our laboratory providing a convenient source of specific DAT, SERT or NET protein for in vitro binding assays. Because it is easy, readily available and provides comparable data for in vitro binding assays, our lab has used the cells expressing the specific transporter instead of membrane homogenates of rat frontal cortex or striatum to screen monoamine transporter inhibitors [29]. The compounds 8-11 synthesized and reported in this paper were subjected to binding evaluations for the monoamine transporters NET, SERT and DAT.…”
Section: Biological Evaluationsmentioning
confidence: 99%
“…A wealth of information on the synthesis of biphenylthiols (1)(2)(3)(4)(5) has been reported in the past few years. 27,28,[30][31][32][33]45,46 The new series of biphenylthiols 28-42 were successfully prepared using schemes 1-3. The synthesis of fluorinated biphenylthiols 28-31 is illustrated in scheme 1.…”
Section: Chemistrymentioning
confidence: 99%
“…Alternatively, the above mixture was irradiated with microwaves at 150°C for 15 min followed by the work-up described earlier gave the desired product. (32) was prepared from 20 as a yellow oil in 87% yield according to general procedure F. 1 (33) was prepared from 21 as a yellow oil in 85% yield according to general procedure F. 1 (34) was prepared from 23 as a yellow oil in 70% yield according to general procedure F. 1 (45) was prepared from 20 as a yellow oil in 94% yield according to general procedure F. 1 (46) was prepared from 21 as a yellow oil in 93% yield according to general procedure F. 1 General Procedure (G) for Selective Reduction of Amide Group-To a solution of amides (45-52 and 32-34) (0.18 mmol) in THF (10 mL) at 0°C, 1.0 M BH 3 -THF (5 eqiuivalent) was added. The mixture was heated to reflux for 1.5-2 hrs.…”
Section: General Procedures (F) For Alkylation With Bromoethanol and Bmentioning
confidence: 99%
“…Therefore, it seems that the introduction of a fluorine atom at R 3 position and substitution of the sulphur by an oxygen in the diphenyl bridge has almost no effect on the affinities, which is in accordance with the reported literature [35] . Moreover, Oya et al [36] showed that compounds with a O(CH 2 ) 2 F, OMe, Br, I, or OH function at R 3 position also displayed high SERT affinities. Therefore, the introduction of a halogen at this part of the molecule does not affect the SERT affinity of the ligands, and the replacement of the halogen atom by a OH, OMe, or O(CH 2 ) 2 F group also affords compounds with nanoto subnanomolar affinities.…”
Section: In Vitro Binding Datamentioning
confidence: 99%